Incidance of Psoriasis in Patients with Different Skin Diseases in Baquba City - Murad, Alaa Aldeen Khorsheed; Hussien, Watheqe Mohammed (Diyala Journal of Medicine, 2018)
Background: Psoriasis is a common, chronic, and recurrent disease characterized by remission and exacerbation in formation of salmon - pink, well demarcated erythematous plaques, covered by white adherent silvery scales, its prevalence varies in different populations from 0.1-11.8% according to published reports . Objective: To study is to estimate the incidence of psoriasis among patients attending dermatological consulting clinic in Baquba teaching hospital. Patients and Methods: A retrospective study was done in outpatient clinic of Baquba Teaching Hospital, which includes patients with different skin diseases attending the clinic during the whole year from first of January to thirty one of December of 2012, they were diagnosed by dermatologists. Patients with psoriasis were evaluated for age and sex. Results: Ten thousands, nine hundred and sixty four patients with different skin diseases were attended to outpatient clinic department of dermatology in Baquba Teaching Hospital for the period from the first of January to the 31 of December 2012, their ages ranged from 2-60 years . Out of this number 220 (2%) patients were diagnosed to have psoriasis. They were 118 (54%) males and 102 (46%) females’ .the disease more in age groups 21-30 years and 31-40 years (30.5% and 23.7% respectively). Conclusion: It was concluded that psoriasis was common in patients with different skin disease in Baquba City and it is the disease of young and adult population.